Alcohol consumption/dependence and resilience in older adults with high blood pressure - Aline Alves dos Santos Dullius; Silvana Maria Coelho Leite Fava; Patrícia Mônica Ribeiro; Fábio de Souza Terra (Universidade de São Paulo, 2018)
ABSTRACT Objective: to evaluate alcohol consumption/dependence and resilience in older adults with high blood pressure and to analyze the factors associated with these variables. Method: a descriptive, cross-sectional, quantitative study developed with 300 older adult patients with high blood pressure from Family Health Strategy units in a municipality of Minas Gerais, Brazil. A semi-structured questionnaire called the Alcohol Use Disorder Identification Test and the Resilience Scale were used. Data were analyzed using the Pearson's chi-square test, Fisher's exact test, Cronbach's alpha, odds ratio and logistic regression. Results: 89.3% of the interviewees were low-risk for consuming alcoholic beverages. The variables gender, age, smoking and disease duration were significantly associated with alcohol consumption/dependence. 36.7% of the people presented a low resilience. The variables family and individual monthly income, education level, physical activity and leisure had an association with resilience. No statistically significant association was observed between alcohol consumption/dependence and resilience. Conclusion: alcohol consumption and resilience can interfere with the physical and mental health of older adults with high blood pressure.